2010
DOI: 10.1093/annonc/mdp260
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of weekly intravenous and intraperitoneal paclitaxel combined with S-1 for advanced gastric cancer with peritoneal metastasis

Abstract: Combination chemotherapy of i.v. and i.p. PTX with S-1 is well tolerated and active in gastric cancer patients with peritoneal metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
188
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(195 citation statements)
references
References 26 publications
5
188
2
Order By: Relevance
“…After a successful phase II trial with gastric cancer patients whose disease was deemed unresectable becasue of confirmed peritoneal metastasis, they conducted a randomized phase III trial with the same population to compare this hybrid regimen with the S-1 and cisplatin combination [6], the current standard of care for treatment of unresectable gastric cancer. Although survival analysis of that trial is about to be conducted, we believe that the current study remains useful to reinforce the rationale for the use of intraperitoneally administered PTX alone or in combination with other drugs to control the peritoneal disease postoperatively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After a successful phase II trial with gastric cancer patients whose disease was deemed unresectable becasue of confirmed peritoneal metastasis, they conducted a randomized phase III trial with the same population to compare this hybrid regimen with the S-1 and cisplatin combination [6], the current standard of care for treatment of unresectable gastric cancer. Although survival analysis of that trial is about to be conducted, we believe that the current study remains useful to reinforce the rationale for the use of intraperitoneally administered PTX alone or in combination with other drugs to control the peritoneal disease postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with peritoneal metastases have seldom been eligible for studies that aim to evaluate new and promising drugs, because the efficacy of chemotherapeutic agents is generally elucidated through treatment of patients with measurable lesions. The efficacy of intraperitoneal administration of paclitaxel (PTX) has been suggested by some phase II trials and pharmacokinetic studies in gastric cancer [4][5][6], but less convincingly than in ovarian cancer [7], another cancer type that is commonly associated with peritoneal metastases. To date, no comparison of intraperitoneal versus intravenous administration of PTX has been attempted for gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
“…After some pilot studies, Ishigami et al57, 58 conducted successive phase I and phase II trials to establish a combination of Sā€1, i.v. paclitaxel, and i.p.…”
Section: Peritoneal Metastasismentioning
confidence: 99%
“…Studies have shown that i.p. administration of paclitaxel is effective in the treatment of gastric cancer with peritoneal metastasis [9][10][11].…”
Section: Introductionmentioning
confidence: 99%